POLA PEMBAGIAN KERJA DAN HUBUNGAN SOSIAL EKONOMI PADA MASYARAKAT KOMUNITAS SUKU AKIT PEKERJA PANGLONG (TUNGKU) ARANG DI DESA BERANCAH KECAMATAN BANTAN KABUPATEN BENGKALIS - Haris Friawan; Hesti Asriwandari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research was conducted in Desa Berancah Kecamatan Bantan Kabupaten Bengkalis. The purpose of this study was to determine the form of socio-economic relations between the owner panglong charcoal with charcoal panglong workers (Suku Akit) in Desa Berancah Kecamatan Bantan Kabupaten Bengkalis. This study entitled "Patterns Division of Labour and Social Affairs at the Economic Community Panglong Worker (Suku Akit) In Desa Berancah Kecamatan Bantan Kabupaten Bengkalis". The focus of research topic What is the pattern of division of labor in the management of panglong charcoal on (Suku Akit) community in Desa Berancah Kecamatan Bantan. Population of this research is all workers panglong. Sampling was done by purposive technique. sample of 12 workers panglong. The author uses descriptive qualitative method and the data were analyzed qualitatively. Instruments Data were observation, interviews and documentation. The results showed that there are four types of division of labor in a charcoal kiln Desa Berancah, as follows: Hunter mangrove wood, wood-burning mangrove, Dismantling and arrange the charcoal from the stove, and Loading charcoal into the space reserved from this research it is known that there are three kinds socio-economic types of relationships formed in the work system panglong in Desa Berancah, namely Please helping, in a working system panglong are social relations typical helping. Typical here because the owners do not want to increase the amount of wages given to workers charcoal kiln owners. However, if in the form of the necessities of life such as the urgent needs of the owner panglong will be happy to help. Bargaining System, a system of bargaining in question is a form of cooperation that is based on the same goal. Between owners and workers charcoal stoves are a bargaining process that is inevitable in determining wages are set and the wages will be accepted. The existence of the Association of collectivity in social relationships, relationships togetherness in question is bound by a common emotional worker among workers. Then the owner panglong have confidence comes from ancestors that the division of labor in the charcoal panglong better done by Suku Akit. Keywords: Division f Labor, Suku Akit, Panglong